The Effect of Loan to Deposit Ratio and Debt to Equity Ratio on Return on Equity - Leni Lawati (Almana : Jurnal Manajemen dan Bisnis, 2021)
ROE level is the main thing for investors and potential investors. Issues of liquidity, performance efficiency, and strengthening of capital are still the main discussions. These can also affect the value of ROE. So that the research aims to determine with certainty the effect of the Loan to Deposit Ratio (LDR) and the Debt to Equity Ratio (DER) on the Return on Equity (ROE) in the Islamic banking sub-sector listed on the IDX for the 2014-2018 period. The independent variables are LDR and DER while ROE is the dependent variable. The method used is quantitative. Meanwhile, the data used in this study is secondary data from the Company's Annual Financial Statements obtained from the official website of the Indonesia Stock Exchange at idx.co.id. Data testing was carried out by descriptive statistical analysis, multiple regression analysis, and hypothesis testing using SPSS. The results showed that partially LDR had a positive and significant effect on ROE and DER had no effect on ROE, while simultaneously LDR and DER had a significant effect on ROE.